Pengembangan Model Aplikasi Manajemen Keuangan Untuk Bisnis Laundry Berbasis UMKM Menggunakan Metodologi Waterfall - Febrianto Pratama, Arif; Noprisson, Handrie (JSAI (Journal Scientific and Applied Informatics), 2024)
The laundry business is a micro, small and medium enterprise (MSME). However, currently, transaction handling, and financial tracking systems in MSME businesses are still manual, namely by writing in books or face-to-face communication. This research aims to develop a laundry service management system application using the waterfall method that can make it easier for owners to receive income and expense reports, transaction processes, and obtain information on business places digitally. The research stage consists of problem analysis, design, implementation and testing. The development method used is the waterfall method and application implementation using the PHP programming language, MySQL as a database, and bootstrap as a framework. Based on the results of the research, the application supports users in viewing reports from each input from the user page, customer page, laundry data, and transaction page. More specifically, the application supports user data management, customer data management (unique codes, customer names, addresses, and mobile phone numbers), transaction data management (number of clothes weight, nominal, laundry status, and other records), report management (transaction notes, income reports, and expense reports) and based on measurements using the blackbox method produces 100% accuracy.